Melittin Inhibition and Eradication Activity for Resistant Polymicrobial Biofilm Isolated from a Dairy Industry after Disinfection - Emilia Galdiero; Antonietta Siciliano; Renato Gesuele; Valeria Di Onofrio; Annarita Falanga; Angela Maione; Renato Liguori; Giovanni Libralato; Marco Guida (International Journal of Microbiology)
The emerging concern about the increase of antibiotic resistance and associated biofilm has encouraged scientists to look for alternative antibiotics such as antimicrobial peptides (AMPs). This study evaluated the ability of melittin to act as an antibacterial biofilm inhibitor and biofilm remover considering isolates from dairy industry. Minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs), minimum biofilm inhibitory concentrations (MBICs), and biofilm removal activities were studied in polymicrobial biofilms produced from isolates. MIC and MBC were set at 1–3 µg/mL and 25–50 µg/mL for Gram-positive and Gram-negative bacteria, respectively. Results demonstrated a good MBIC reaching 85% inhibition ability and a good activity and better penetration in deeper layers against the mixed preformed biofilm, thereby increasing its activity against all isolates also at the lowest tested concentrations. Melittin showed interesting characteristics suggesting its potential to act as an antimicrobial agent for polymicrobial biofilm from dairy industry even in environmental isolates.